Novel structure of GaAs-based interdigital-gated HEMT plasma devices for solid-state THz wave amplifier - Hashim, Abdul Manaf; Kasai , Seiya; Iizuki, Kouichi; Hashizume, Tamotsu; Hasegawa, Hideki (Elsevier, 2007)
Theoretical analysis of potential distribution in the interdigital-gated high electron mobility transistor (HEMT) plasma wave device was carried out. The dc I-V characteristics of capacitively coupled interdigital structure showed that uniformity of electric field under the interdigital gates was improved compared to the dc-connected interdigital gate structure. Admittance measurements of capacitively coupled interdigital gate structure in the microwave region of 10-40 GHz showed the conductance modulation by drain-source voltage. These results indicate the existence of plasma wave interactions.